APA YANG TIDAK BOLEH KITA LUPAKAN (Memori dalam Tradisi Lisan Massomba Tedong) - Susia Imanuella (Kementerian Pendidikan dan Kebudayaan, 2020)
ABSTRACTAs one manifestation of intangible cultural heritage, the oral tradition that preserves various kind of human experiences does not only exist as narratives of events in the past, but in the form of traditional ceremonies, oral traditions become a representation of the past which cannot be separated from the situation and conditions today, when this tradition is spoken. The oral tradition of massomba tedong, which became a part of Tongkonan consecration ceremonies in Toraja has a crucial meaning for the Torajans' life. Not only to recall the memory regarding their origin and identity as a group of indigenous peoples, but the tradition of massomba tedong is also presented to strengthen the